Histoires d’enveloppe. Considérations médicales et artistiques sur la peau - Vinit, Florence (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2008)
The skin is both the most important organ of the human body and that which defïnes the physical exterior of an individual. The skin can be conceived as an envelope, representing personal finitude and as well as acting as a sign of subjective existence. This article examines representations of this "envelope" in Western culture, with a particular emphasis on contemporary art. Contemporary artists such as Pat Moore, Helmut Newton, Stelarc, Simon Costin, Orlan, and Gina Pane investigate the possibilities offered by biotechnology to eliminate the skin as a physical boundary and symbol of the body. By referencing the work of these artists, the author discusses how their imaginative engagement with the idea that skin is not a limit of the body can transform the way we view our "being in the world."